Sodium-glucose co-transporter 2 inhibitors: a pleiotropic drug in humans with promising results in cats - Vieira, Aline B.; Cavanaugh, Sarah M.; Ciambarella, Bianca T.; Machado, Marcus V. (Frontiers in Veterinary Science, 2025)
Diabetes mellitus is a common metabolic disease in humans and cats. Cats share several features of human type-2 diabetes and can be considered an animal model for this disease. In the last decade, sodium-glucose transporter 2 inhibitors (SGLT2i) have been used successfully as a class of hypoglycemic drug that inhibits the reabsorption of glucose from the renal proximal tubules, consequently managing hyperglycemia through glycosuria. Furthermore, SGLT2i have been shown to have cardiac, renal, and other protective effects in diabetic humans acting as a pleiotropic drug. Currently, at least six SGLT2i are approved by the Food and Drug Administration (FDA) for use in humans with type-2 diabetes, and recently, two drugs were approved for use in diabetic cats. This narrative review focuses on the use of SGLT2i to treat diabetes mellitus in humans and cats. We summarize the human data that support the use of SGLT2i in controlling type-2 diabetes and protecting against cardiovascular and renal damage. We also review the available literature regarding other benefits of these drugs in humans as well as the effects of SGLT2i in cats. Adverse effects related to the use of these hypoglycemic drugs are also discussed.